2018
DOI: 10.1007/s10584-018-2145-y
|View full text |Cite
|
Sign up to set email alerts
|

National-scale analysis of low flow frequency: historical trends and potential future changes

Abstract: Article (refereed) -postprint Kay, A.L.; Bell, V.A.; Guillod, B.P.; Jones, R.G.; Rudd, A.C. 2018. Nationalscale analysis of low flow frequency: historical trends and potential future changes. Climatic Change, 147 (3-4). 585-599. AbstractThe potential impact of climate change on hydrological extremes is of increasing concern across the globe. Here a national-scale grid-based hydrological model is used to investigate historical trends and potential future changes in low flow frequency across Great Britain. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…NFM planning should also consider potential effects on low flows/droughts, which are themselves expected to worsen under climate change (e.g. Kay et al 2018). While there are limitations to the evidence presented here, this paper presents a novel method for evaluating the potential of NFM to offset the impacts of climate change on peak flows, and when the evidence base is enhanced a more robust assessment will be possible.…”
Section: Discussionmentioning
confidence: 99%
“…NFM planning should also consider potential effects on low flows/droughts, which are themselves expected to worsen under climate change (e.g. Kay et al 2018). While there are limitations to the evidence presented here, this paper presents a novel method for evaluating the potential of NFM to offset the impacts of climate change on peak flows, and when the evidence base is enhanced a more robust assessment will be possible.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of full water system closure may introduce biases in future projections of drought, most notably due to the off-line computation of potential 10.1029/2019GL081967 evapotranspiration (Kay et al, 2018;Milly & Dunne, 2017). The lack of full water system closure may introduce biases in future projections of drought, most notably due to the off-line computation of potential 10.1029/2019GL081967 evapotranspiration (Kay et al, 2018;Milly & Dunne, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, this reform might also enforce more restrictive low flow conditions during drought than those presented here, in which river flow triggers are based on a historical monthly varying threshold of the low river flow conditions from a baseline period. As highlighted in previous studies (Kay et al, ), reductions in river flows are expected in the future. In contrast to this conventional variable threshold approach in which the thresholds do not adjust to the hydrological consequences of a changing climate, Wanders et al () applied a nonstationary transient variable threshold in which the threshold is based on the river flow of the previous 30 years.…”
Section: Discussionmentioning
confidence: 64%
“…G2G has been shown to perform well for a wide variety of catchments across Britain (Bell et al, ) and has recently been shown to perform well specifically for low flows and for historical drought identification (Rudd et al, ). The weather@home2 hydrological data set has been used to analyze potential future changes in low flows and drought characteristics (Kay et al, ).…”
Section: Methodsmentioning
confidence: 99%